Incentives and legal barriers for power-to-hydrogen pathways: An international snapshot. (3rd May 2019) - Dolci, Francesco; Thomas, Denis; Hilliard, Samantha; Guerra, Carlos Fúnez; Hancke, Ragnhild; Ito, Hiroshi; Jegoux, Mathilde; Kreeft, Gijs; Leaver, Jonathan; Newborough, Marcus; Proost, Joris; Robinius, Martin; et al.
Abstract: Rendering the energy system more sustainable can only be achieved through a combination of low-carbon energy production, energy efficiency, and coupling of energy sectors. In this context, Power-to-Hydrogen concepts for managing supply and demand, providing seasonal storage, and being the linking element between different sectors (electricity generation, gas grids, transport and industry), has attracted significant interest during the last decade. However, the deployment of technology is subject to legal barriers, which may differ from one region to another. On the contrary, there may be incentives to facilitate market introduction of a new technology. In this paper, an international network of experts under the umbrella of Task 38 of the International Energy Agency's Hydrogen Technology Collaboration Programme assesses the legal framework in ten countries regarding power-to-hydrogen applications. The most frequently considered pathway, from a legal standpoint, is using hydrogen for mobility applications. Only a few countries are implementing legal frameworks for diverse hydrogen applications. Highlights: Low-carbon H2 can play a role in the electric, gas, transport, and industry sectors. This paper provides a snapshot of the legal context for power-to-H2 in 10 countries. The most acknowledged pathway, from a legal standpoint, is mobility applications. Only few countries are implementing legal frameworks for diverse H2 applications.